2022
DOI: 10.1017/s0007114522004032
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium supplementation alleviates low salinity stress in the Pacific white shrimp Litopenaeus vannamei: growth, antioxidative capacity and hepatopancreas transcriptomic responses

Abstract: Selenium (Se) is an essential trace element associated with animal growth and antioxidant and metabolic processes. However, whether Se, especially organic Se with higher bioavailability, can alleviate the adverse effects of low salinity stress on marine economic crustacean species has not been investigated. Accordingly, juvenile Pacific white shrimp (Litopenaeus vannamei) were reared in two culture conditions (low and standard salinity) fed diets supplemented with increasing levels of L-selenomethionine (0.41,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Additionally, Gallegos et al reported that incubation with 345.86 ng/mL SS markedly increased the mRNA stability of thioredoxin reductase, a homodimeric Sec-containing protein, in HT-29 colon cancer cells [34]. Consistent with previous studies, our results indicated that both SS and SM could improve the mRNA stabil- As Se serves as an important component of GPx [30], its activity was also detected. As shown in Figure 1B,C, both 100 ng/mL SS and SM significantly enhanced GPx activity (p < 0.01).…”
Section: Effects Of Ss and Sm On The Mrna Stability And Protein Synth...supporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, Gallegos et al reported that incubation with 345.86 ng/mL SS markedly increased the mRNA stability of thioredoxin reductase, a homodimeric Sec-containing protein, in HT-29 colon cancer cells [34]. Consistent with previous studies, our results indicated that both SS and SM could improve the mRNA stabil- As Se serves as an important component of GPx [30], its activity was also detected. As shown in Figure 1B,C, both 100 ng/mL SS and SM significantly enhanced GPx activity (p < 0.01).…”
Section: Effects Of Ss and Sm On The Mrna Stability And Protein Synth...supporting
confidence: 91%
“…As Se serves as an important component of GPx [ 30 ], its activity was also detected. As shown in Figure 1 B,C, both 100 ng/mL SS and SM significantly enhanced GPx activity ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%